Duisburg and its port, endpoint of China's silk road - Pascha, Werner (OrdnungsPolitisches Portal, 2021)
The question to what extent the EU, Germany, its regional states or individual localities can and should cooperate with China has gained considerable importance recently. This paper discusses the city of Duisburg, an important logistics hub in western Germany, next to the rivers Rhine and Ruhr, as a particularly interesting case study. Its location is ideal as the
10419/233896
Keywords: Graue Literatur; Duisburg; China; New silk road; Belt and Road Initiative; regional economic development